BEYOND THE ANSWER: MAKING SENSE OF NEUROPRUDENCE - KAMALNATH, Anthea Jay (Journal of Advanced Research in Law and Economics, 2017)
A favourite uncle wants to borrow money from you but he is a compulsive gambler. In three years, he has gone through nearly a million dollars, depleting all of his savings. His life and marriage are just about on the rocks. His only child has no resources to finance her college education. As you sit there looking at him, figuring out your answer, no fewer than twenty of your brain structures and their circuits are busily at work. Your long-term memory (stored in the cerebral cortex) dredges up recollections of your many talks with your uncle, as well as time spent together attending the Yankee games when you were a child. Recent conversations with him (part of your short-term memory and stored in your hippocampus) and your aunt’s chronic kidney disease also surface to make you feel sorry for him and his family. Sympathy for him gets a strong boost as your visual cortex and mirror neurons (including the superior temporal sulcus, the fusiform gyrus, and the amygdala) process your uncle’s facial expressions and his embarrassment over needing money. The amygdala is also activated when you experience a twinge of fear as you perceive that your refusal of his request could cause a rift as damaging to his family as the path he is on. Fuelled by disappointment and anger, your ambivalence activates your premotor cortex, which rehearses throttling him. Your frontal lobe and anterior cingulated cortex step in to stifle the throttle impulse. The problem-solving function of these structures understands that some addictions are impervious to intervention; you thus reason that you might just as well give him the money and keep his affection. Your prefrontal cortex, on the other hand, steps in to take command and sorts out how to deliver a gentle, loving ‘no.’ This winds up activating other regions of the cerebral cortex – visual (occipital cortex and superior temporal sulcus, spurious colliculus), auditory (temporal cortex), language (Broca’s and Wernicke’s areas) – as your prefrontal lobe reviews all the sensations you’ve received and develops a plan of response. Finally you will experience his reaction to your ‘no’. This will activate your sensory systems (auditory and visual), limbic structures – in particular the amygdala (emotional reaction to his affect), hippocampus (connecting memory to emotions), as well as anterior cingulate cortex (self-control), and hypothalamus (bodily response such as sweating, increased heartbeat) – and the frontal lobes. Fortunately, both you and your uncle are blissfully unaware of these processes (Tancredi 2007, 41-42).